Naming concepts: evidence of two routes. - Roth HL; Nadeau SE; Hollingsworth AL; Cimino-Knight AM; Heilman KM (Neurocase (Taylor & Francis Ltd), 2006)
This study examines a parallel distributed processing (PDP) model (partly based on the Wernicke-Lichtheim information processing model) that posits two routes for naming concepts, whole word and phonological. To test the two naming route hypothesis of this model, we performed confrontation naming tests that were either uncued, semantically cued, or phonologically cued in a patient with naming impairment due to Broca's aphasia. In spoken language and in uncued naming to confrontation, word retrieval was severely impaired and marked by semantic but no phonemic paraphasic errors. With semantic cues, naming behavior was unchanged; however, with phonological cues, naming success was enhanced but frequent phonemic paraphasias were produced. These results suggest that the patient spontaneously engaged the whole word naming route, but when given phonological cues, he engaged an alternative phonological naming route that incorporated phonological sequence knowledge.